Technology assessment of the Office of the Ombudsman's Lifestyle Check Hotline Prospect for Improvement and Enhancement of the Agency's Hotline System - Diaz, Angel Joseph S. (University of the Philippines Diliman, 2012)
The Technology Assessment of the current process for the Ombudsman Lifestyle Check Hotline (OLCH) resulted in the identification of promising points for improvement, and guidelines for the enhancement of its day to day operations. Primarily, this study revealed that the operational problems of the OLCH are caused by the limitations of the ICT equipment and the absence of complementary technologies for the same to work at the desired level and expected results. Accordingly, the weaknesses of the OLCH include (but not limited to) lack of data tracking, referencing and management system, poor response time due to the limitations of the mobile phone; absence of Mobile to PC connectivity, and missing resources such as internet connection to address queries and other concerns, especially of callers/texters. Benchmarking from the cases of the Civil Service Commission (CSC) and the Department of the Interior and Local Government (DILG), the OLCH can address its issues by considering, choosing, and adapting the processes which these two (2) government agencies employ. In the case of the CSC, the agency made use of its Management Information System to create a simple but effective system of data tracking and management. This in-house developed application enabled the agency to save resources (time, money and effort) insofar as system acquisition and hotline operations are concerned. Moreover, partnering with a service provider solved the issue of intermittent disconnections and procurement of a mobile phone. On the other hand, the DILG's hotline operations employ a web based text messaging platform which requires only a computer and internet connection to operate. This system allows a client-configured automated operation and provides an online database in managing received and sent messages. Further, this system enjoys the provision of a 24/7 operating hours, thus catering SMS received beyond office hours ans during weekends/holidays. Evidently, both systems of the CSC and DILG are found to be more appropriate to the needs of a hotline center than the current set up of the OLCH. Fortunately, there are opportunities for the OLCH to address its weaknesses and enhance its operations. For instance, the presence of the OMB's MISS can augment creation of a simple but working database for the use of the (i) hotline agent in tracking calls and texts and the (ii) OMB Management in generating reports and corresponding statistics. Also, the presence of OMB Internet can also address lack of internal information resources and can provide access to internet connection in serving information concerns of the OLCH's clients. Nevertheless, all recommendations identified in this study are deemed to enhance the OLCH's operations and strategically improve OMB's effort in complying with its mandate. The creation of the Ombudsman Lifestyle Check Hotline (OLCH) has been one of the reforms and initiated projects in order to amplify active and conscious participation of the different stakeholders- government, civil society and the public - in this war against corruption. The hotline provides a venue where the public and other government agencies can report information or leads and/or file complaints against erring public officials. Thus, it is on this premise that this study stands by belief that the problems of the OLCH, if not addressed immediately, would eventually affect and forfeit its abovementioned purpose. Technology as a "tool" does not mean just employing technology resources for a specific goal, but having the "appropriate" technology to get the job done.